PENGARUH LUAS RUANG TERBUKA HIJAU TERHADAP PENURUNAN NO2 BERDASARKAN NILAI TOTAL KOLOM CITRA SATELIT GOME 2 METOP-B - Raden Kokoh Haryo Putro; Aussie Amalia; Novirina Hendrasarie (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
The use of fossil fuels for motor vehicles in Indonesia has the potential to produce air emissions that can pollute the environment, especially human health. The parameter that is often used as a reference for pollution by motor vehicle emissions is NO2. Nowadays satellite imagery has been developed and used in various fields. One of them is to monitor air quality. Analysis of the effect of the ratio of the area of ​​Green Open Space (RTH) in the cities of Surabaya and Jakarta to the reduction of NO2 was carried out in this study. The method of this study is using tropospheric NO2 data based on the total NO2 column data from satellite imagery GOME 2 METOP B. The results show that there is an influence of the area of the green open space ratio on the pattern of NO2 increase in DKI Jakarta and Surabaya.